Websites, data types and information privacy concerns: A contingency model. Issue 7 (November 2017) - Tang, Jih-Hsin; Lin, Yi-Jen
Highlights: This study explored and empirically examined the relationships of Website types, data types and information privacy concerns by two online surveys in Taiwan. One set of data was collected Facebook.com; the other was from Ruten.com (Taiwan's version of eBay). Results showed that Website type (relational vs. transactional) and data type (required vs. optional) were dominant factors of individual's information privacy concerns (collection, improper access, errors and unauthorized secondary use). The interaction effect of Website type and data type was also significant, implying that users of a social-networking showed higher concerns on their personal information (optional data) to be collected; however, users of a transactional site concerned more about the unauthorized secondary use and improper access of their required data. Moderating variables such as gender, age, use and experiences of being cheated online were also collected and analyzed. A contingency model of information privacy concerns was developed and validated.